Reading habit and gender as predictors of adult learners’ performance in english language in literacy centers in Oyo state, Nigeria (2024)
Reading is an effort to understand the writer's message for development on a personal level and professional achievement. As a result, psychologists view it as a complex cognitive process where meanings are constructed from texts. The current study was carried out in literacy centres in Oyo State, Nigeria, to ascertain the associations between adult learners' academic accomplishment in English language, gender, and reading habits. A descriptive survey design was used in the study. The study employed a purposive sampling technique to choose 120 participants from literacy centers located in the city of Ibadan. Data were gathered using the Reading Habits Questionnaire (RHQ) and the English Language Achievement Test (ELAT). Descriptive and inferential statistics were used to analyze the responses. The empirical findings indicated that reading habit (β = -0.097; t = -0.277; p 0.783 > 0.05) and gender (β = -0.526; t = -1.577; p 0.119 > 0.05) have negative and insignificant relationship with adult learners’ academic performance. The results also indicated reading habit and gender jointly accounted for 0.04% of the total variance in the dependent variable (adult learners’ performance in the English language) among adult learners in literacy centers in Oyo State. Lastly, the findings revealed that age significantly influences adult learners ’ performance in the English language (F3,17 = 2.46; P<0.05). It is implied that adult educators should design these kinds of projects and assignments with reflective thinking in mind, taking into account the importance of reading habits for academic success. In addition, facilitators could collaborate to develop schedules for library instruction to help adult learners develop a reading habit.